Molecular characterization of pseudomonodelphic dagger nematodes of the genus Xiphinema Cobb, 1913 (Nematoda: Longidoridae) in Costa Rica, with notes on Xiphinema setariae Tarjan, 1964 - Peraza-Padilla, Walter (2016)
Pseudomonodelphic dagger nematodes of the genus Xiphinema are characterized by having one of the genital branches reduced and lacking an ovary. They are usually reported from tropical regions. Nematode surveys conducted during rainy seasons in Costa Rica resulted in detection of several Xiphinema costaricense populations, but also other pseudomonodelphic and didelphic species of Xiphinema. We undertook detailed integrative morphometric and molecular studies using D2-D3 expansion segments of 28S rDNA, and ITS1-rDNA. From those studies, we also identified several populations of Xiphinema krugi and two populations of Xiphinema setariae with characteristics in agreement with those of the original and later descriptions of these species. The phylogenetic analyses of these species with other representatives of Xiphinema spp. indicated that pseudomonodelphic species are phylogenetically related (X. costaricense and X. krugi). On the basis of ITS1 sequences of X. costaricense and X. variegatum from Brazil, as well as similar morphology and morphometrics of both species, the latter is proposed here as a junior synonym of the former. Also, our morphometric data showed some intraspecific variability within X. setariae, which in combination with the molecular evidence, suggests that X. setariae and X. vulgare need to be considered as a single taxon.